Nationally Accredited Journal Management Assistance and Training for Journal Managers Throughout the City of Palangka Raya - Saptono, Mofit; Anwar, Harles; Tarantang, Jefry; Kurniawan, Rahmad; Akbar, Wahyu (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2023)
The purpose of this training is to increase the understanding of journal managers regarding journal management, especially with regard to national and international indexing, and improve journal management competence (skills) related to how to manage journals, especially related to national and international indexing. Based on the results of the analysis of the responses of the training participants, it can be concluded that: The scientific journal management training that was carried out was very useful in improving the quality of scientific journal management in the IAIN Palangka Raya area in particular and in the city of Palangka Raya in general. of course Have a direct positive impact on increasing the acceptance of scientific journals. In addition, from the participants' responses during the training and mentoring it was concluded that: Improving the quality of management of scientific journals is a very basic component affecting the quality of published journals